Antioxidant Effect of Livomap, A Polyherbal Formulation on Ethanol Induced Hepatotoxicity in Albino Wistar Rats - Kanchana. G and Jayapriya .K (Journal of Applied Pharmaceutical Science, 2013)
The present study was designed to evaluate the antioxidant activity of Livomap on ethanol induced hepatotoxicity in albino wistar rats. A total of 30 rats were divided into five groups of six rats in each group. Group 1 served as normal control, Group 2 - normal rat + livomap (50mg/Kg), Group 3 - ethanol control rats, Group 4 - ethanol + livomap (25mg/Kg) and Group 5 - ethanol + livomap (50mg/Kg). The liver toxicity was induced by the administration of ethanol to the animals at a dose of 3 g/kg orally for 35 days. During the period, livomap was co-administered to the rats at doses of 25 and 50 mg/kg for 35 days. Ethanol induced rats exhibited significant increase in the levels of lipid peroxidative products and decrease in the levels of antioxidants. Co-administration of livomap to ethanol-induced rats significantly minimized the alterations in the levels of lipid peroxidation products and antioxidants. Results suggest that livomap might be beneficial in alleviating ethanol-induced oxidative damage and may be attributed to the antioxidant property of polyherbal formulation.
Keywords: Antioxidant, Ethanol, Hepatoprotective, Lipid peroxi